Pengaruh Service Quality dan Customer Value terhadap Kepuasan Nasabah Produk Tabungan Pendidikan di Bank Syariah Indonesia KCP Suropaticore - Intan Siti Holipah; Ida Rapida; Armansyah M. Sarusu (Jurnal Dimamu, 2023)
This research is motivated by the fluctuating number of customer data for education savings products. Based on the results of observations and interviews, research shows that the cause of the fluctuation in the number of customer data for education savings products is influenced by Service Quality and Customer Value at Bank Syariah Indonesia Suropaticore Sub-Branch Office. This study aims to determine how the influence of Service Quality and Customer Value on Customer Satisfaction of Education Savings Products at Bank Syariah Indonesia Suropaticore Sub-Branch Office. Either partially or simultaneously. The object of this research is the customer of educational savings products at Bank Syariah Indonesia Suropaticore Sub-Branch Office. The type of this research is quantitative with associative approach. This type of data uses primary data and uses data collection techniques through questionnaires and complementary data through observation, interviews, documentation, literature studies and questionnaires. The sampling technique in this study used non-probability sampling, amounting to 75 people. The results of this study indicate that there is an effect of Service Quality on Customer Satisfaction of Education Savings Products where tcount > ttable value (10.576>1,66629). Customer Value where tcount > ttable value (4.799>1,66629). has a significant effect on Customer Satisfaction of Education Savings Products where tcount > ttable value. Simultaneously Service Quality and Customer Value have a significant effect on Customer Satisfaction of Education Savings Products where F count = 56.063 > F table = 2,73.